Joachim Du Bellay: a closed or open understanding of history? - Pintarič, Miha (Slavia Centralis, 2021)
The Ruins of Rome is a collection of poetry by Joachim Du Bellay, written in the style called sublime, which is an exception rather than a rule for this poet. Elsewhere in his work he claims to be a poet of the low style who would gladly leave the other style to Ronsard. The Ruins of Rome picture this city from a variety of aspects, usually in comparison with something else (e. g. the seven wonders of the ancient world are compared to the seven hills of Rome). All these details put together compose an authentic brief history of the city. Du Bellay is not, however, interested in history in itself, but in its meaning. This will be Christian with a fair share of Neo-platonic and Stoical influence, but it remains to be seen what its eclectic ‘mixture’ will be.